Odds of fussy eating are greater among children with obesity and anxiety. (7th August 2021) - Thorsteinsdottir, Sigrun; Olafsdottir, Anna S.; Brynjolfsdottir, Berglind; Bjarnason, Ragnar; Njardvik, Urdur
Abstract: Background: Fussy eating has been associated with autism spectrum disorder (ASD), attention‐deficit/hyperactive disorder (ADHD), anxiety, and depression. Despite these disorders being prevalent in obesity treatment, no studies have been published on the association of fussy eating in children with obesity and these disorders. Understanding fussy eating in children with obesity and comorbid disorders is important as acceptance of healthy foods tends to be low, especially in children with sensory sensitivities. Objectives: Investigate the prevalence of fussy eating in a cross‐sectional sample of children with obesity and ASD, ADHD, anxiety, and depression; and whether they were more likely to be fussy eaters, comparing those with and without these disorders. Methods: One hundred and four children referred to family‐based obesity treatment in Iceland 2011–2016, mean age 12.0 (SD = 3.0), mean body mass index standard deviation score 3.5 (SD = 0.9). Binary logistic regression was used to estimate the relationship between fussy eating and disorders, adjusting for medication use. Results: A large minority (41.6%) were fussy eaters and 48.9% had at least one comorbid disorder. Over a third of children rejected bitter and sour tastes, and 1.9% and 7.9% rejected sweet and salty tastes, respectively. Compared with those without disorders, the odds of being a fussy eater were increased by a factor of 4.11 when having anxiety (95% confidence intervals) (1.02–16.58, p = 00.046), adjusting for medication use. The odds of being a fussy eater were not increased for other disorders; ASD, ADHD, or depression. Conclusions: In children attending obesity treatment, fussy eating was common. Clinical care models in pediatric obesity treatment should address fussy eating, especially in children with anxiety.